KING’s SCIENCE AND STRENGTHENING THE COMMUNITY : CASE STUDY OF SARA PHANG SUBDISTRICT ADMINISTRATION ORGANIZATION BAN THAEN DISTRICT CHAIYAPHUM. - ดวงธิสาร อภิชิต (Pathumthani University Academic Journal, 2020)
The purposes of the research are 1) To study the normal of Sara Phang Sub district Administrative Organization Ban Thaen District Chaiyaphom Province. Concerning with King’s science and strengthening the community in government management, mainstream development and alternative currents. 2) To study its problems 3) To study how to strengthen the community. This is the qualitative research based on written documents, interview, group discussion and observation with local management, community leaders, Chairman of local community group, villager philosopher total of 20 people. The result revealed that 1) The normal of Sara Phang Sub district Administrative Organization Ban Thaen District Chaiyaphom Province was Creating a holistic network of all parties in the sector increasing, the capacity to solve problems of the local community, the promoting holistic participation in all dimensions and knowledge management and systematic study of information . 2) Its problems were lack of support in knowledge management transfer without being attached to textbooks, lack of support for mews and technology database systems, lacking support in relationships and caring and lacking honesty, honesty to each other Unity and consideration of common interests. 3) The processes to achieve on community strength and stability should be guidelines for appropriate environmental rehabilitation, adaptation to keep up with the changes a happy, stable prosperous and sustainable existence and guidelines for sufficiency, self-sufficiency, and applying sufficiency economy philosophy